Neutralization of ARCoV-induced sera against SARS-CoV-2 variants. Issue 6 (30th November 2022) - Li, Xiao-Feng; Zhang, Na-Na; Li, Yu-Hua; Cao, Shou-Chun; Zhang, Yi-Fei; Qin, Cheng-Feng
ABSTRACT: ARCoV is a candidate mRNA vaccine encoding receptor-binding domain of SARS-CoV-2. Its safety, tolerability, and immunogenicity profile have been confirmed in the phase 1 clinical trial in China. A multi-regional phase 3 clinical trial is currently underway to test the efficacy of ARCoV (NCT04847102). Here, we tested the cross-neutralization against SARS-CoV-2 variants of concern (VOCs) of a panel of serum samples from participants in the phase 1 clinical trial of ARCoV by pesudo- and authentic SARS-CoV-2. Our data suggest the immunity induced by the ARCoV vaccine reduced but still has significant neutralization against the Alpha and Delta variants. Moreover, ARCoV maintained activity against the Beta variant, despite of its obvious reduction in neutralizing titers. Our findings further support the solid protective neutralization activity against VOCs induced by ARCoV vaccine.